2015
DOI: 10.1186/s13068-015-0255-6
|View full text |Cite
|
Sign up to set email alerts
|

New generation biofuel: continuous acidogenesis of sucrose-raffinose mixture simulating vinasse is promoted by γ-alumina pellets

Abstract: BackgroundThis investigation comprises a contribution on the production of a new generation biofuel using the industrial liquid waste of bioethanol distilleries, known as vinasse. This study focuses on the exploitation of vinasse as an acidogenesis substrate for volatile fatty acids and simultaneous ethanol production. These products can be used for ester production, which is the new generation biofuel. Therefore, the aims of the present study are (i) to examine any promotional effect of γ-alumina on acidogene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
13

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 15 publications
1
7
0
13
Order By: Relevance
“…The final VFAs concentration was comparable to that reported in a study where vinasse was used for VFAs production (19 g L -1 of total VFAs) 26 . Furthermore, comparable VFAs overall concentration was obtained when the same process was carried out using non-dephenolised GP as the substrate (about 23 g L -1…”
Section: Vfas Productionsupporting
confidence: 83%
“…The final VFAs concentration was comparable to that reported in a study where vinasse was used for VFAs production (19 g L -1 of total VFAs) 26 . Furthermore, comparable VFAs overall concentration was obtained when the same process was carried out using non-dephenolised GP as the substrate (about 23 g L -1…”
Section: Vfas Productionsupporting
confidence: 83%
“…Here, the substantial simultaneous ethanol formation along with OAs in the case of acidogenesis of pure carbohydrates in the presence of promoters, also has to be highlighted (Syngiridis et al, 2013, Lappa et al, 2015a, 2015b. However, ethanol formation in the case of the raw materials (vinasse, whey and cellulose) was very low.…”
Section: Technological Considerationmentioning
confidence: 96%
“…Previous studies have reported the simultaneous production of OAs and ethanol during anaerobic acidogenesis of synthetic media containing glucose (Ren et al, 1997;Syngiridis et al, 2013Syngiridis et al, , 2014. Furthermore, very good OAs productivities were obtained during acidogenesis of vinasse, the main liquid waste of the ethanol industry (Lappa et al, 2015a(Lappa et al, , 2015b.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Experiments in comparison to free cells systems showed that g-alumina promoted the simultaneous production of acetic acid and ethanol. The promoting effect of porous materials, like g-alumina pellets, in methane [67] alcoholic [68] and acidogenic fermentations [69] is known. The simultaneous production of VFAs and ethanol is of high technological importance since they can be used in esterification reactions to produce ethyl esters of low molecular weight.…”
Section: Promotion Of the Anaerobic Digestion Acidogenic Stepmentioning
confidence: 99%